2023
DOI: 10.1186/s12967-023-03962-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of the impact of lncRNA AI662270 during the development of atherosclerosis

Abstract: Background Atherosclerosis is driven by synergistic interactions between pathological biomechanical and lipid metabolic factors. Long noncoding RNAs (LncRNAs) have been implicated in atherogenesis. The purpose of this study was to investigate the potential mechanism of lncRNA AI662270 on macrophage cholesterol transport in atherosclerosis. Methods Apolipoprotein E deficiency (ApoE−/−) mice were fed a high fat diet for 16 weeks to construct atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In fact, we observed a radical decline in Bcl2l11 expression when Morrbid was upregulated ( Figure 7B ). Among the downregulated lncRNAs, eight had at least one citation; AI662270 , AU020206 , and Snhg15 were of particular interest ( Figure 7C ), as it has been reported that AI662270 and AU020206 are involved in the atherosclerosis induced by macrophages ( 33 , 34 ) and Snhg15 is involved in inflammation ( 35 ).…”
Section: Resultsmentioning
confidence: 78%
“…In fact, we observed a radical decline in Bcl2l11 expression when Morrbid was upregulated ( Figure 7B ). Among the downregulated lncRNAs, eight had at least one citation; AI662270 , AU020206 , and Snhg15 were of particular interest ( Figure 7C ), as it has been reported that AI662270 and AU020206 are involved in the atherosclerosis induced by macrophages ( 33 , 34 ) and Snhg15 is involved in inflammation ( 35 ).…”
Section: Resultsmentioning
confidence: 78%
“…In addition, both AI662270 and the lncRNA Mexis are highly expressed during the progression of atherosclerosis [ 67 ]. AI662270 accelerates the progression of atherosclerosis by directly binding to Abca1 to attenuate Abca1 expression and activity and inhibiting SR-BI expression to promote foam cell formation [ 68 ]. Mexis promotes the coactivator action of DDX17, which enhances LXR-mediated Abca1 expression, resulting in increased cholesterol efflux from macrophages, which in turn affects atherosclerotic plaque development [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between diet and AS, and there is evidence that the intake of specific foods can reduce AS risk (Riccardi et al, 2022). Astaxanthin is a common nutrient that has been reported to have AS-protective effects, and a recent study demonstrated that the protective effect of astaxanthin on AS arises through the CircTPP2/miR-3073b-5p/ABCA1 axis that promotes macrophage cholesterol efflux and thus reduces foam cell formation (Zhang Z. et al, 2023). In addition, the side effects of some drugs used to treat other diseases may contribute to AS, and ncRNAs may be crucial regulators of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…AI662270 overexpression promotes lipid accumulation, reduces the cholesterol outflow of macrophages, and accelerates the formation of foam cells, yielding an AS-promoting effect. AI662270 knockdown exerts a therapeutic effect on AS (Hong et al, 2023). Moreover, there is evidence that MIAT can affect lesion formation and plaque destabilization in AS.…”
Section: Lncrnas Act As Molecular Sponges In the As Processmentioning
confidence: 99%